DIE UNTERSCHEIDUNG ZWISCHEN DER GÖTTLICHEN ESSENZ UND DER NATÜRLICHEN ENERGIE GOTTES NACH PHILOTHEOS KOKKINOS IN SEINEN ZWEI REDEN ÜBER DAS TABORLICHT GEGEN AKINDYNOS - KAPRIEV, Georgi (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
This article explores the elaboration of the distinction between the divine essence and the essential energies of God in the two Orations on the Light of Tabor by Philotheos Kokkinos, directed against Gregory Akindynos and the Akindynists. Herein it is shown that Kokkinos follows a well thought out process of philosophizing when dealing with those dimensions of oikonomia (the activity of God in the world) that correspond directly to the realm of what is, par excellence, theologia (or God in himself). Within this framework, Kokkinos correctly formulates the main theses that provoked the opposition of the Akindynists to the distinction between the divine essence and the essential energies of God. These main points are elaborated through the coining of formulae (quite faithful to the authentic teaching of Gregory Palamas) that are occasionally more precise than the formulations of Palamas himself. Moreover, Kokkinos deals with the conceptual and practical dimensions of the distinction between the essence and the essential energies, without, however, exceeding the limits of the logic contemporary to him.